Perancangan Sistem Informasi Keuangan Berbasis Web Multi User Dengan UML - Rusydi Umar; Sarjimin Sarjimin; Arief Setyo Nugroho; Achmad Dito; Indra Gunawan (Jurnal Algoritma, 2020)
STIE XYZ in managing financial transactions still uses Microsoft Excel which is divided by year and type of payment. The purpose of this research is to build a systemized alternative application for managing financial transactions in accordance with financial management at STIE XYZ. Rapid Application Development (RAD) system development method was chosen because in this method a system can be developed within 180 days and the users are directly involved when developing the system so that the system is developed according to user needs. The RAD design process uses the Unified Modeling Language (UML) method. Dimension of Quality for Goods (Operations, Reliability and Durability, Conformance, Service Ability, Appearance and Perceived, and Quality) test scores> 75.50, 76.50 so that it can be concluded that the product is declared successful, the results of the benefit testing are based on the variables Usability, Learnability, Efficiency and Acceptability (ULEA) produces a value> 70 that is 90.65% so that it can be declared useful. Keywords: Finance, RAD, UML, ULEA